Web based Instruction for Immersion Class in Alauddin State Islamic University of Makassar - Farida Farida; Supardi Supardi; Jumardin Muchtar (Naifaderu Cipta Sejahtera, 2023)
Purpose This study aims to understand web-based instruction for immersion to students. It is intended to identify the use of the web on zoom media and websites to hone students' English language skills to improve students' fluency in English language skills. Methodology Furthermore, this study was conducted in the English education department at the State Islamic University of Alauddin Makassar where English is used as the language of instruction. The class consisted of 15 students. In addition, this study used qualitative methods. Results/Findings The results showed that This immersion instruction is relatively frequent and strong because before the lecturer starts in class, the lecturer performs the act of speaking English and prepares the material to be given to students by giving specific instructions so that students can skillfully communicate in the presented English. Furthermore, students learn through videos guided by native speakers and hone their English-speaking skills with confidence. Thus, it can be said that students are quite enthusiastic to practice speaking English and can follow the instructions with the immersion learning system on video media and the application of immersion program on speaking skills is quite effective for communication between students by using 3D website so that students can hone their speaking skills with native speakers in virtual 3-dimensional form. Implications Implementing web-based instruction in immersion classes not only opens doors to a more versatile and accessible learning environment but also demonstrates the potential for enhanced engagement and interactive language acquisition methodologies.